Troublesome Trimes: Potential cryptic speciation of the Trimeresurus (Popeia) popeiorum complex (Serpentes: Crotalidae) around the Isthmus of Kra (Myanmar and Thailand) - Mulcahy, Daniel G.; Lee, Justin L.; Miller, Aryeh H.; Zug, George R. (Zootaxa, 2017)
The taxonomic identity of the Trimeresurus (Popeia) popeiorum complex from the Isthmus of Kra and to the north was investigated. Several studies over the last decade have produced several specimens and associated mtDNA sequence data for a variety of individuals of the T. popeiorum and “T. sabahi” complexes. Here, we combine four mitochondrial genes (12S, 16S, ND4, and CytB) from all available specimens in GenBank with the addition of five new specimens collected from the mainland, Tanintharyi Region of Myanmar. Maximum Likelihood and Bayesian analyses identified that T. popeiorum sensu lato is paraphyletic with two geographically distinct clades: a northern clade representing populations from northern Myanmar, Laos and northern Thailand and a southern clade representing samples from the Tanintharyi Region and adjacent west Thailand. While the two clades have considerable genetic distance, they appear to be morphologically identical, leading to the hypothesis that the southern clade represents a cryptic, undescribed species. Because they appear to be cryptic species and the limitation of only five specimens from the southern lineage, this does not permit us to formally describe the new species. In accordance to past molecular studies, we uncovered paraphyly and lack of genetic support for the validity of taxa within the T. sabahi complex. However, we suggest recognizing these populations as subspecies within T. sabahi.